Co-simulation of a HVAC system-integrated phase change material thermal storage unit. Issue 3 (4th May 2017) - Jones, A.T.; Finn, D.P.
Abstract : A co-simulation environment, consisting of a detailed mathematical model of a thermal energy storage unit which is incorporated with an EnergyPlus simulation model of a full building HVAC system, is described. The two models are integrated using the user-defined plant component feature in EnergyPlus and the Building Controls Virtual Test Bed (BCVTB) environment. The thermal energy storage unit, which consists of encapsulated phase change material in a series of flat plates and a heat transfer working fluid (water), is modelled using a transient one-dimensional forward finite difference method. The thermal storage model is executed within MATLAB and is verified against experimental data, showing a discharging heat transfer accuracy to within 2.5%. The building model, which incorporates a retrofitted ground source heat pump system within a thermally massive building, is simulated in the EnergyPlus environment. The co-simulation arrangement allows for in-depth analysis of the integrated system under dynamic operating conditions, which is currently not possible within the EnergyPlus environment. Moreover, the overall adopted approach, based on generic integration of a detailed mathematical model, using a third party generalised programming environment, into an established building simulation environment, serves as a successful exemplar for other researchers and practitioners working in the field.